Residue Analysis and the Effect of Preharvest Forchlorfenuron (CPPU) Application on On-Tree Quality Maintenance of Ripe Fruit in “Feizixiao” Litchi (Litchi chinensis Sonn.) - Liu, Xin-Sheng; Luo, Ye-Cheng; Wang, Si-Wei; Wang, Hui-Cong; Harpaz-Saad, Smadar; Huang, Xu-Ming (Frontiers in Plant Science, 2022)
Litchi is a highly perishable fruit. Ripe litchi fruit lose quality quickly as they hang on tree, giving a very short hanging life and thus harvest period. This study attempted to explore roles of cytokinin in regulating fruit ripening and senescence of litchi and examine the possibility of applying cytokinin in “on-tree storage” of the fruit. Exogenous cytokinin, forchlorfenuron (CPPU), was applied at 20 mg L-1 7 weeks after full bloom on litchi (Litchi chinensis cv. Feizixiao) fruit clusters. Color parameters, chlorophylls, anthocyanins, fruit and fruit part weights, total soluble solutes, soluble sugars, organic acids, non-anthocyanin flavonoids, ethanol as well as CPPU residue in fruit were traced. CPPU residue was higher but decreased faster in the pericarp than in the aril, where it maintained <10 μg kg-1. CPPU had no significant effect on fruit weight but tended to increase pericarp weight. The treatment suppressed chlorophyll loss and anthocyanin accumulation in the pericarp, increased non-anthocyanin flavonoids in the aril, but had no significant effects on non-anthocyanin flavonoids in the pericarp and total sugar and organic acids in the aril. As the commercially ripe fruit hanged on tree, total soluble solutes, total sugar and sucrose decreased with ethanol and acetic acid accumulation in the aril. CPPU significantly suppressed sucrose and thus total sugar loss and ethanol and acetic acid accumulation in the aril and malondialdehyde accumulation in the pericarp of the overripe fruit. Soluble invertase, alcohol deydrogenase and pyruvate decarboxylase activity and gene expression in the aril were down regulated by CPPU. The results suggest that cytokinin partially suppresses the ripening process in litchi and is effective to slow quality loss in overripe fruit on tree.